Evolution of Gene Duplication in Plants. Issue 4 (10th June 2016) - Panchy, Nicholas; Lehti-Shiu, Melissa; Shiu, Shin-Han
Abstract : Gene duplicates are prevalent in plants and in some cases contribute to evolutionary novelty. Abstract: Ancient duplication events and a high rate of retention of extant pairs of duplicate genes have contributed to an abundance of duplicate genes in plant genomes. These duplicates have contributed to the evolution of novel functions, such as the production of floral structures, induction of disease resistance, and adaptation to stress. Additionally, recent whole-genome duplications that have occurred in the lineages of several domesticated crop species, including wheat ( Triticum aestivum ), cotton ( Gossypium hirsutum ), and soybean ( Glycine max ), have contributed to important agronomic traits, such as grain quality, fruit shape, and flowering time. Therefore, understanding the mechanisms and impacts of gene duplication will be important to future studies of plants in general and of agronomically important crops in particular. In this review, we survey the current knowledge about gene duplication, including gene duplication mechanisms, the potential fates of duplicate genes, models explaining duplicate gene retention, the properties that distinguish duplicate from singleton genes, and the evolutionary impact of gene duplication.